The effects of shift-work schedules on the sleep, health, safety, and quality of life of police employees during the COVID-19 pandemic - James, Lois; James, Stephen; Atherley, Loren (Frontiers in Psychology, 2023)
Introduction The negative health and safety consequences of police fatigue are increasingly recognized as a critical problem. This study’s objective was to measure the effects of different shift schedules on police employee health, safety, and quality of life. Methods A cross sectional research design surveyed employees (N = 319) from a large, U.S. west coast municipal police service during the fall of 2020. The survey was made up of a battery of validated instruments designed to assess dimensions of health and wellness (e.g., sleep, health, safety, and quality of life). Results We found 77.4% of police employees had poor sleep quality, 25.7% had excessive daytime sleepiness, 50.2% had PTSD symptoms, 51.9% had depressive symptoms, and 40.8% had anxiety symptoms. Working night shifts significantly decreased sleep quality and increased excessive sleepiness. Furthermore, employees working night shifts were significantly more likely to report falling asleep at the wheel while driving home than employees working other shifts. Discussion Our findings have implications for interventions designed to promote police employee sleep health, quality of life, and worker safety. We urge researchers and practitioners alike to target night shift workers, to help mitigate these risks.